The process of determining driving safety in people with dementia: A review of the literature and guidelines from 5 English speaking countries. (October 2019) - Walsh, Liam; Chacko, Emme; Cheung, Gary
Objectives: To review literature and guidelines related to the process of determining driving safety in people with dementia. Method: Four electronic databases were searched in December 2016/January 2017. We limited our search to literature and guidelines published in the UK, USA, Canada, New Zealand and Australia. Results: General practitioners are primarily responsible for driver licensing; however, they often feel ill-equipped and it can compromise the therapeutic relationship. Occupational therapist driving assessment is considered as the 'gold-standard' but is costly and often not available. Medical advisory boards assist the assessment process by providing independent licencing decisions. Conclusions: General practitioner training, funding for occupational therapist driving assessment and the establishment of a medical advisory board could be considered to improve the current practice of driving assessment in dementia.